Effect of Hot Electron Stress on AlGaN/GaN HEMTs of Hydrogen Poisoning - J. He; Y. Q. Chen; Z. Y. He; Y. F. En; C. Liu; Y. Huang; Z. Li; M. H. Tang (IEEE Journal of the Electron Devices Society)
We have investigated the effect of hot electron stress on the electrical properties of AlGaN/GaN high electron mobility transistors (HEMTs) of hydrogen poisoning. The AlGaN/GaN HEMTs were biased at the semi-on state, and they suffered from the hot electron stress. The devices of hydrogen poisoning were degraded, while there is almost no degradation for the fresh ones. The hot electron stress leads to the significantly positive shift of threshold voltage and the notable decrease of drain-to-source current for the AlGaN/GaN HEMTs of hydrogen poisoning. For the AlGaN/GaN HEMTs of hydrogen poisoning, the trap density increases by about one order of magnitude after the hot electron stress experiment. The physical mechanism can be attributed to electrically active traps due to the dehydrogenation of passivated point defects at AlGaN surface, AlGaN barrier layer, and heterostructure interface. The results of this paper may be useful in the design and application of AlGaN/GaN HEMTs.